PERAN KONTRAKTOR DALAM PENINGKATAN CONSTRUCTABILITY PADA PROYEK KONSTRUKSI GEDUNG BERTINGKAT DI JABODETABEK - Fransiskus Jeremy Koswara; Hendrik Sulistio (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2023)
Constructability enhancements is an effort to improve construction projects’ performance by implementing knowledges and experiences of expert project participants. The purpose of this study was to determine the correlation between the contractor's performance and the implementation of constructability enhancements prnciple, especially in the main phase of the project which is the construction phase of the building in Jabodetabek. The method used in this study is descriptive quantitative, where collected research data in the form of questionnaires’ responses has to be validated by experts through Focus Group Discussions (FGD). The research data were analyzed by linear regression test and Relative Importance Index (RII). The results obtained from this study are that there is a relatively strong positive correlation between the contractor's performance and the implementation of constructability enhancements principle in construction projects in Jabodetabek. The linear regression equations obtained from the results of data processing are Y = -20,338 + 4,938 X, and in its implementation in the field which tested by the RII method, shows that the efforts to enhance constructability related to material scheduling and project documentation are the efforts that have the best implementation in construction projects in Jabodetabek. Abstrak Peningkatan constructability merupakan suatu upaya dalam proyek untuk meningkatkan kinerja dalam pelaksanaan proyek konstruksi dengan pengimplementasian pengetahuan serta pengalaman para partisipan ahli proyek. Tujuan dilakukan penelitian ini adalah mengetahui korelasi antara performa peran kontraktor di lapangan dengan terlaksananya peningkatan constructability khususnya dalam bidang pelaksanaan pada proyek konstruksi gedung bertingkat di Jabodetabek. Metode yang digunakan merupakan deskriptif kuantitatif, dimana pengumpulan data penelitian berupa kuesioner harus divalidasi oleh pakar melalui Focus group Discussion (FGD). Data penelitian dianalisis dengan uji regresi linear dan Relative Importance Index (RII). Hasil yang diperoleh dari penelitian ini adalah terdapat korelasi positif yang tergolong kuat antara performa peran kontraktor dengan terlaksananya peningkatan constructability dalam proyek di Jabodetabek. Adapun persamaan regresi linear yang didapatkan dari hasil pengolahan data adalah Y = -20,338 + 4,938 X, serta dalam pelaksanaan nya di lapangan yang diuji dengan metode RII menunjukan bahwa upaya peningkatan constructability yang berkaitan dengan penjadwalan material serta pendokumentasian pelaksanaan dalam proyek merupakan upaya-upaya yang memiliki pelaksanaan paling baik dalam proyek konstruksi di Jabodetabek.